Податкове стимулювання підприємництва при наданні державної допомоги: господарсько-правовий аспект - Сіюшов, Денис Юрійович (Одеса, 2021)
У роботі досліджується господарсько-правовий аспект податкового стимулювання підприємництва при наданні державної допомоги. Здійснено комплексний аналіз господарсько-правових засад податкового стимулювання підприємницької діяльності, особливостей закріплення і надання податкових стимулів і пільг у розрізі законодавства України про державну допомогу, нормативного регулювання державної допомоги стосовно податкових пільг у законодавстві Європейського союзу та практики його застосування Судом Європейського союзу

У роботі доведено необхідність визнання на державному рівні, поряд із фіскальною та регулюючою функціями, стимулюючої і стримувальної функцій оподаткування для підприємницької діяльності, що дозволить державі ефективніше розмежовувати спрямованість заходів податкової політики і, відповідно, впроваджувати такі заходи залежно від поставлених цілей.

Розглянуто практику дотримання принципів пропорційності, правової визначеності та законних очікувань при розгляді справ стосовно податкових пільг як державної допомоги Судом ЄС, обґрунтовано використання принципу законних очікувань вітчизняними судами для забезпечення захисту прав підприємців-бенефіціарів у випадках зміни законодавства про державну допомогу чи визнання її незаконною.

Розроблено конкретні пропозиції щодо удосконалення господарського та податкового законодавства з метою досягнення стимулюючого ефекту для підприємництва від державної допомоги, що надається у формі податкових пільг

The paper investigates the economic and legal aspect of tax benefits for enterprises in the provision of state aid. The complex analysis is carried out regarding the economic and legal bases of tax stimulation of business activity, features of granting tax benefits and incentives in the context of the legislation of Ukraine on the state aid, normative regulation of the state aid concerning tax inventives in the European Union legislation and practice of its application by the CJEU.

In the paper it is proved that there exists a need for recognition at the state level, along with fiscal and regulatory functions, stimulating and de-stimulating functions of business taxation, which shall allow the state to more effectively differentiate the direction of tax policy measures and, accordingly, implement such measures depending on the objectives.

The main attention is paid to elucidating the socio-economic content of tax incentives, their legal nature, attributes, forms of existence, the grounds for their provision and determining their impact on entrepreneurial activity. A distinction is made between tax benefits and tax incentives based on term structure, target group of recipients, the presence of state enforcement, monitoring / control by the state over their application, etc. The domestic and foreign practice of the implemented forms of tax incentives in the context of the provision of state aid is investigated in order to establish their advantages, disadvantages and the ability to achieve a stimulating effect for entrepreneurship and promote investment attraction.

The place of taxes, tax benefits and incentives in the mechanism of state regulation of economic activity is studied, the basic economic principles of building a system of legal regulation of taxation of enterprises are analyzed. The paper proves the need to harmonize the provisions of the Economic Code of Ukraine and the Tax Code of Ukraine for the correct interpretation of tax benefits through the system of tax measures in the form of differentiation of tax rates, reduction of the tax base, change or exclusion of the taxable object, as well as the establishment of differences from tax incentives, which will contribute to the improvement of the tax mechanism, stimulating, unshadowing the economy, reducing indirect budget costs associated with the negative impact of anti-competitive norms, harmonizing Ukrainian legislation with EU legislation in terms of providing state aid, etc.

Taking into account the legislation and the latest practice of the EU institutions, the criteria for recognizing tax incentives as a state aid and the rules / features of their application for determining the presence / absence of state aid is analyzed, the need for their application by the courts of Ukraine when considering cases of state aid is articulated, based on the provisions of Article 264 of the Association Agreement between Ukraine and the EU. Based on these criteria, discriminatory provisions of treaties on the avoidance of double taxation, the implementation of which can be recognized as state aid, have been identified.

The practice of observing the principles of proportionality, legal certainty and legal expectations when considering cases regarding tax benefits as state aid by the EU Court is considered, the use of the principle of legal expectations by domestic courts is substantiated to ensure the protection of the rights of beneficiary enterprises in cases of changes in the legislation on state aid or its recognition as illegal.

The paper articulates the need to prepare explanations of the Antimonopoly Commettee of Ukraine on the attributes of state aid and criteria for its determination, grounds for recognition of tax incentives as a state aid and cases when an entity / authorized body is recognized as a provider of state aid, in order to form a unified practice of application by the Antimonopoly Commettee of Ukraine of legislation on state aid, taking into account the practice of CJEU.

Specific proposals have been developed to improve economic and tax legislation in order to achieve a stimulating effect for entrepreneurship from state aid granted in the form of tax incentives.
Сіюшов Д. Ю. Податкове стимулювання підприємництва при наданні державної допомоги: господарсько-правовий аспект. – Рукопис. Дисертація на здобуття наукового ступеня кандидата юридичних наук за спеціальністю 12.00.04 – господарське право; господарсько-процесуальне право. – Національний університет «Одеська юридична академія», Одеса, 2021
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; податкове стимулювання підприємництва; податковий стимул; податкова пільга; державна допомога; державна підтримка; отримувач державної допомоги; надавач державної допомоги; угода про уникнення подвійного оподаткування; принцип законних очікувань; tax incentives for enterprises; tax incentive; tax benefit; state aid; state support; recipient of state aid; provider of state aid; agreement on avoidance of double taxation; principle of legitimate expectations; налоговое стимулирование предпринимательства; налоговая льгота; государственная помощь; соглашение об избежании двойного налогообложения; принцип законных ожиданий